Case report: Movement-related neuroplasticity in a patient after spinal cord injury in response to task-oriented bimanual training - Ma, Di; Zeng, Roy Rongyue; Chan, Sofina Sy; Pan, Yu; Zhang, Jack Jiaqi (Frontiers in Human Neuroscience, 2025)
BackgroundBimanual motor training is an effective neurological rehabilitation strategy. However, its use has rarely been investigated in patients with paralysis caused by spinal cord injury (SCI). Therefore, we conducted a case study to investigate the effects of robot-assisted task-oriented bimanual training (RBMT) on upper limb function, activities of daily living, and movement-related sensorimotor activity in a patient with SCI.MethodsA patient with bilateral upper limb paresis due to incomplete cervical SCI underwent 20 sessions of RBMT. Functional recovery was measured using clinical scales for upper limb motor function and activities of daily living. Training-induced neuroplasticity was evaluated using event-related desynchronization (ERD) induced by movement of the right hand (the more affected side), recorded on the electroencephalogram (EEG).ResultsRBMT improved the patient’s upper limb motor function and activity independence. At baseline, our EEG paradigm demonstrated an ipsilateral predominance of movement-related ERD responses over the sensorimotor cortex (SMC) in relation to the moving hand. Following the RBMT, the ERD pattern shifted from being predominantly ipsilateral to a contralateral allocation.ConclusionThe present case study provides preliminary evidence to support the therapeutic use of RBMT to restore upper limb function in patients with incomplete SCI. The recovery of function following SCI might be related to the rebalancing of sensorimotor activation.